2010
DOI: 10.1016/j.sbi.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ligand diffusion in globins: simulations versus experiment

Abstract: SummaryComputer simulations in molecular biophysics describe in atomic detail structure, dynamics, and function of biological macromolecules. To assess the quality of these models and to pick up new mechanisms, comparisons with experimental measurements are made. Most comparisons examine thermodynamic and average structural properties. Here we discuss studies of dynamics and fluctuations in a protein. The diffusion of a small ligand between internal cavities in myoglobin, and its escape to solvent are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 56 publications
2
60
0
Order By: Relevance
“…More than 50 years of research have culminated in Mb becoming one of the most studied proteins in the field of structural biology (4). The histidine gate hypothesis and the role played by alternative ligand migration paths have been examined in detail by both experimental and theoretical methodologies but are still surrounded by controversy (5). It would be impractical to describe all the available data, and instead, we will attempt to summarize the key observations and discrepancies.…”
mentioning
confidence: 99%
“…More than 50 years of research have culminated in Mb becoming one of the most studied proteins in the field of structural biology (4). The histidine gate hypothesis and the role played by alternative ligand migration paths have been examined in detail by both experimental and theoretical methodologies but are still surrounded by controversy (5). It would be impractical to describe all the available data, and instead, we will attempt to summarize the key observations and discrepancies.…”
mentioning
confidence: 99%
“…Previous studies have characterized gas diffusion in myoglobin (16)(17)(18)(19), (reviewed in ref. 20), lipoxygenase (21), flavin-containing monooxygenase (22) and oxidases (22,23) (reviewed in ref. 24), and hydrogenase (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Historically, globins have served as a model system for understanding how ligand flux through heme protein scaffolds controls gas-binding properties. Over the past 50 y, studies on myoglobin have utilized X-ray crystallography (9), time-resolved absorption techniques (10), CO photolysis of protein crystals (11,12), and computational methods (13,14) to provide a detailed molecular picture of ligand migration through the globin fold. Experimental approaches have implicated a histidine residue, the "His(E7) gate" (15), as the primary route for ligand entry and exit, in contrast to computational studies that have identified multiple ligand migration pathways (14).…”
mentioning
confidence: 99%